Case Report: Multiple extragenital adenomatoid tumors in the rectum and small intestinal mesentery - Wang, Zhongqian; Xiaoyan, Lei; Fu, Tianxu; Wang, Zhenping; Luo, Shishi (Frontiers in Oncology, 2026)
Adenomatoid tumors (ATs) are benign tumors commonly found in the genital organs, usually occurring as a single mass with a good prognosis after surgery. However, multiple extragenital ATs are extremely rare, often asymptomatic, and may lead to misdiagnosis. This case report describes a patient with multiple ATs involving the rectum and small intestinal mesentery. The patient was a 39-year-old man who had been suffering from abdominal pain and recurrent loose stools for 6 months. Diagnostic contrast-enhanced computed tomography (DCE-CT) of the abdomen and pelvis showed multiple cystic–solid masses with uneven density and patchy enhancement at the edges. The patient underwent laparoscopic total excision, and postoperative pathology confirmed multiple extragenital ATs in the rectum and small intestinal mesentery. The patient recovered well, and no recurrence was observed during a 17-month follow-up. This case aims to raise awareness of the imaging features of multiple ATs in rare extragenital locations, preventing misdiagnosis, missed diagnosis, and excessive treatment.